An asymptotic model for elastoplasticity - Howell, P; Ockendon, H; Ockendon, J (Springer Netherlands, 2014)
This paper describes the asymptotic analysis of a model for one-dimensional elastoplastic compression at high stress. We identify a new wave phenomenon that can occur when a singular asymptotic limit reduces the order of a nonlinear hyperbolic system.